2023
DOI: 10.1037/adb0000861
|View full text |Cite
|
Sign up to set email alerts
|

Impact of discrimination and coping on Veterans’ willingness to seek treatment for physical and mental health problems.

Abstract: Objective: This study aimed to provide insight into health disparities among Veterans by (a) documenting the prevalence of physical and mental health problems in a racially diverse sample of Veterans, (b) comparing Veterans' willingness to seek treatment for various physical and mental health conditions, and (c) examining the impact of discrimination and coping on willingness to seek treatment. Method: Veterans reported on current physical and mental health symptoms and the importance of treatment for various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…In contrast, White veterans demonstrated relatively low rates of insomnia (58%) and relatively high interest in treatment (80%). Complementing our findings that veterans as a group are least willing to seek treatment for the conditions that are most prevalent in their communities (Miller, Monk, et al, 2022), these data indicate that participants from racial/ethnic groups with the highest need for insomnia treatment are also among the least interested. Given these findings, providers are especially encouraged to screen for sleep problems and offer sleep treatment among veterans of colour, as these minoritised groups may not share sleep issues spontaneously or request sleep treatment unprompted.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, White veterans demonstrated relatively low rates of insomnia (58%) and relatively high interest in treatment (80%). Complementing our findings that veterans as a group are least willing to seek treatment for the conditions that are most prevalent in their communities (Miller, Monk, et al, 2022), these data indicate that participants from racial/ethnic groups with the highest need for insomnia treatment are also among the least interested. Given these findings, providers are especially encouraged to screen for sleep problems and offer sleep treatment among veterans of colour, as these minoritised groups may not share sleep issues spontaneously or request sleep treatment unprompted.…”
Section: Discussionsupporting
confidence: 79%
“…Based on data in civilian samples (Chen et al, 2015; Grandner et al, 2010; Kaufmann et al, 2016), we hypothesised that Black, Hispanic/Latine and Asian veterans would demonstrate higher rates of insomnia than non‐Hispanic White veterans. Our previous research found that veterans (as a group) demonstrate the concerning combination of high rates of sleep problems with comparatively low interest in treatment (Miller, Monk, et al, 2022). To inform future research in this area, we examined this discrepancy (rates of sleep problems versus interest in treatment) across racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…In heavy‐drinking samples, interest in treatment for emotional problems is significantly greater than interest in treatment for alcohol‐related problems (Capron et al, 2018). Indeed, both heavy‐drinking adults and individuals with substance use disorders (SUD) are more willing and/or likely to seek care for co‐morbid conditions than for substance use (Edlund et al, 2012; Miller et al, 2022). One co‐morbid health condition that is prevalent among those who use alcohol/other drugs and tends to be less stigmatised than substance use is sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%